Evaluation of Barriers to Implementation of Environmental Education with Fuzzy FUCOM Technique - Baki, Rahmi (International Journal of Social Sciences Perspectives, 2022)
In this study, in order to examine the significance and encourage the adoption of Environmental Education (EE), it is fundamentally important to determine the strength and levels of the obstacles encountered in the EE process and to present the proposed solution. First of all, with the literature review, the factors that were found to affect the EE process in the past studies were determined. Then, a new subjective weighting method called the fuzzy Full Consistency Method (FUCOM) was used to determine the criterion weights of the obstacles. The final values of the weight coefficients were obtained using the GAMS/CPLEX package program. As a result of the application, it was determined that the most important obstacles encountered during the implementation of EE are financial inadequacies, lack of transportation, safety, responsibility, and classroom management, lack of content information, and lack of natural science knowledge. Based on the findings obtained in the last part of the study, recommendations were made for the dissemination of EE.